Development of psychological readiness to work with gifted children for preschool institution teachers - Bondarchuk, Olena; Dovgan, Natalia (Social Welfare: Interdisciplinary Approach, 2013)
The article presents a model of pre-school teachers’ psychological readiness to work with gifted children. The program of a special course designed for extensive development of readiness and teachers’ training to work with gifted children is presented. The effectiveness of the developed program is confrmed by a formative experiment. The obtained results can become a basis for psychological activities aimed at such readiness formation.